2020
DOI: 10.3390/su122410489
|View full text |Cite
|
Sign up to set email alerts
|

Through Sport to Innovation: Sustainable Socio-Economic Development in European Countries

Abstract: Using clustering and principal component analysis, we demonstrate that—at the national level in Europe—innovativeness correlates strongly to both social capital and participation in sport. In this aspect, countries such as the Scandinavian countries and the countries of Central and Eastern Europe differ visibly. Referring to prior empirical research, we claim that a causal relation between sports, through social capital, and innovativeness can be established. In the context of social capital accumulation, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although many countries actively promote citizens' participation in physical activity in various degree, many studies found that social differentiation of participation in physical activity exists due to difference of religion background, policies and economic development in different countries [38][39][40]. Researchers focusing on the influence factors of sports participation from different countries obtained various conclusions and a large number of studies have showed that family influence [41], socio-economic background [42], capital support [43] and income are the important factors among the sports participation and have close relationship with sports behavior. Ruseski and Maresova [44] conducted an international comparative analysis of physical activity participation data from 34 countries/regions and also found that income, education level, hours worked were closely related to physical exercise participation.…”
Section: Discussionmentioning
confidence: 99%
“…Although many countries actively promote citizens' participation in physical activity in various degree, many studies found that social differentiation of participation in physical activity exists due to difference of religion background, policies and economic development in different countries [38][39][40]. Researchers focusing on the influence factors of sports participation from different countries obtained various conclusions and a large number of studies have showed that family influence [41], socio-economic background [42], capital support [43] and income are the important factors among the sports participation and have close relationship with sports behavior. Ruseski and Maresova [44] conducted an international comparative analysis of physical activity participation data from 34 countries/regions and also found that income, education level, hours worked were closely related to physical exercise participation.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, given that frequent changes of leadership personnel lead to organizational instability [5][6][7], football clubs may endanger their performance improvement due to constant within-season turnover decisions. Consequently, the social [8,9], organizational [10], and economic [11] sustainability of football clubs tend to be compromised depending on how managerial decisions are taken, such as when employers opt for consecutive personnel replacements based on superficial analyses.…”
Section: Introductionmentioning
confidence: 99%